Defecation enhances cerebral perfusion and delays fatigue in elite triathletes. Issue 1 (31st December 2023) - Wei, Chen-Chan; Condello, Giancarlo; Yang, Ai-Lun; Yu, Szu-Hsien; Liao, Yi-Hung; Chen, Chung-Yu; Hsu, Chi-Chieh; Huang, Chi-Yang; Kuo, Chia-Hua
ABSTRACT: Background: Rectal distension increases regulatory burden to autonomic nervous system in the brain. Purpose: To determine the effect of rectal defecation on endurance performance and blood supply to the prefrontal brain and sub-navel regions of elite triathletes. Methods: Thirteen elite triathletes completed a cycling time trial (80% VO2max ) under defecated and non-defecated conditions, using a counterbalanced crossover design. Oxygenation and blood distribution in prefrontal brain and sub-navel regions were monitored by near-infrared spectroscopy (NIRS) during cycling. Results: Defecation moderately decreased systolic blood pressure (−4 mmHg, p < 0.05, d = 0.71), suggesting an alleviation of autonomic nervous activity. During the exercise trials, fatigue (cycling time to exhaustion) occurred when cerebral oxygenation decreased to 5 % below baseline regardless of treatment conditions, suggesting a critical deoxygenation point for sustaining voluntary exertions. Cerebral blood (estimated by total hemoglobin) increased progressively throughout the entire exercise period. Defecation decreased sub-navel oxygenation levels below the non-defecated level, suggesting an increased sub-navel oxygen consumption. Exercise also decreased sub-navel blood distribution, with minimal difference between non-defecated and defecated conditions. Defecation improved blood pooling in the prefrontal brain during exercise ( p < 0.05) and enhanced cycling performance in triathletes (Non-defecated: 1624 ± 138 s vs. defecated: 1902 ± 163 s, d = 0.51, p < 0.05). Conclusion: Our results suggest that improved exercise performance after defecation is associated with greater blood availability to compensate deoxygenation in the prefrontal brain region during exercise. Further investigation is needed to examine the role of increasing sub-navel oxygen consumption in the performance improvement after defecation.